The Effectiveness of Celengan Rindu in Monitoring Fetal Movement in Third-Trimester Mothers - Dian Roza Adila; Vella Yovinna Tobing; Mardeni Mardeni (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims:  Neonatal mortality ranks fifth among the top ten causes of death in the world, including neonatal conditions. Early detection measures, such as assessing the well-being of the fetus during the womb through monitoring Fetal Movements (FM), can help to reduce the incidence of IUFD. Monitoring FM aims to determine fetus well-being. Celengan Rindu application was created with the goal of making it easier for mothers to monitor FM daily. This study to determine the efficacy of Celengan Rindu in monitoring FM in third-trimester mothers at the Sidomulyo Inpatient Health Center. Methods:  This study was carried out quantitatively on Celengan Rindu using a quasi-experimental design and FM monitoring. This study's sample included up to 30 pregnant women in their third trimester. The sampling technique used was accidental sampling with a questionnaire designed by the researcher himself regarding monitoring FM. The Wilcoxon test was used to analyze the data in this study. Results:   Most of the pregnant women 66.7%, were in their early adulthood and had gravida status, with the majority being primigravida, 63.3%. Only 16.7% of respondents monitored FM according to the results of the pretest before using the Celengan Rindu. The post-test showed that 25 people monitoring fetal movements out of 30 respondents. The P-value was 0.001, it means Celengan Rindu was effective to monitor FM.  Conclusions: Celengan Rindu can be used to prevent IUFD and provide the results of a successful pregnancy, allowing the mother to proceed with the expected delivery process.